2017
DOI: 10.2337/db16-0881
|View full text |Cite
|
Sign up to set email alerts
|

PDGFRβ Regulates Adipose Tissue Expansion and Glucose Metabolism via Vascular Remodeling in Diet-Induced Obesity

Abstract: Platelet-derived growth factor (PDGF) is a key factor in angiogenesis; however, its role in adult obesity remains unclear. In order to clarify its pathophysiological role, we investigated the significance of PDGF receptor β (PDGFRβ) in adipose tissue expansion and glucose metabolism. Mature vessels in the epididymal white adipose tissue (eWAT) were tightly wrapped with pericytes in normal mice. Pericyte desorption from vessels and the subsequent proliferation of endothelial cells were markedly increased in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 44 publications
4
62
0
1
Order By: Relevance
“…Therefore, it has been assumed that pericytes represent WAT progenitors, and proper PdgfRβ signaling is required to guarantee progenitor potential (Olson and Soriano, 2011;Tang et al, 2008). However, the importance of PdgfRβ was recently challenged in a report by Onogi and colleagues that indicated that Pdgf signaling is only indirectly involved in adipose tissue expansion via the formation of blood vessels (Onogi et al, 2017).…”
Section: Pericytesmentioning
confidence: 99%
“…Therefore, it has been assumed that pericytes represent WAT progenitors, and proper PdgfRβ signaling is required to guarantee progenitor potential (Olson and Soriano, 2011;Tang et al, 2008). However, the importance of PdgfRβ was recently challenged in a report by Onogi and colleagues that indicated that Pdgf signaling is only indirectly involved in adipose tissue expansion via the formation of blood vessels (Onogi et al, 2017).…”
Section: Pericytesmentioning
confidence: 99%
“…Reduced lipid storage can reflect decreased nutrient intake or increased energy expenditure, as well as changes in growth factors that directly or indirectly control lipid storage in adipocyte (Boucher et al, 2016;Hu et al, 2015;Huang et al, 2009;Molgat et al, 2009;Onogi et al, 2017;Pang et al, 2008;Seki et al, 2018;Shook et al, 2018;Sottile and Seuwen, 2000). In support of the latter, a qPCR analysis of growth factors that control lipid storage in white adipocytes (Boucher et al, 2016;Hu et al, 2015;Huang et al, 2009;Molgat et al, 2009;Onogi et al, 2017;Pang et al, 2008;Seki et al, 2018;Shook et al, 2018;Sottile and Seuwen, 2000) indicate that expression of Pdgfc and Igf1 are strongly reduced in fat pads from mutant mice as compared to control littermates (Figure 2F). Expression of Vegfb and Bmp2 is also reduced but to a lesser extent (Figure 2F).…”
Section: Reduced Pdgfcc In Adipose Tissue Of Mice Lacking Tissue Resimentioning
confidence: 99%
“…These include receptors such as PDGFRB (MIM: 173410) and TGFBR2 (MIM: 190182), the insulin growth factor IGF1 (MIM: 147440) and its binding partners IGFBP2 (MIM: 146731) and IGFBP3 (MIM: 146732), and the CXCR4 chemokine (MIM: 162643). [47][48][49][50][51][52][53] Furthermore, two of the enhancers harboring archaic variants at the highest frequencies interact with key adipocyte-differentiation regulators, such as KLF3 (MIM: 609392) and PRRX1 (MIM: 167420), 54,55 suggesting that introgression at AdMSC might have been adaptive in humans. In support of this notion, Dannemann and colleagues have found that more than half of aSNPs associated with gene expression in subcutaneous adipose tissue had increased in frequency over the last 10,000 years, whereas the majority of aSNPs had decreased in frequency over the same period of time.…”
mentioning
confidence: 99%